The Process and Product of Coherence Monitoring in Young Readers: Effects of Reader and Text Characteristics - Currie, Nicola K.; Francey, Gillian; Davies, Robert; Gray, Shelley; Bridges, Mindy S.; Restrepo, Maria Adelaida; Thompson, Marilyn S.; Ciraolo, Margeaux F.; Hu, Jinxiang; Cain, Kate (Scientific studies of reading, 2021)
We examined sixth graders' detection of inconsistencies in narrative and expository passages, contrasting participants who were monolingual speakers (N = 85) or Spanish-English DLLs (N = 94) when recruited in pre-kindergarten (PK). We recorded self-paced reading times and judgments about whether the text made sense, and took an independent measure of word reading. Main findings were that inconsistency detection was better for narratives, for participants who were monolingual speakers in PK, and for those who were better word readers. When the text processing demands were increased by separating the inconsistent sentence and its premise with filler sentences there was a stronger signal for inconsistency detection during reading for better word readers. Reading patterns differed for texts for which children reported an inconsistency compared to those for which they did not, indicating a failure to adequately monitor for coherence while reading. Our performance measures indicate that narrative and expository texts make different demands on readers.